Public enemies - Korman, Gordon (New York : Scholastic, 2005)
Aiden and Meg Falconer have been chased from state to state by the FBI, and by a killer they know only as Hairless Joe but now as they are closing in on the truth behind their parents arrest they are finding it harder to elude their pursuers.
"Chase #5."
"An Apple paperback."
009-012.
790
Accelerated Reader AR
Keywords: Fugitives from justice -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Adventure fiction